Propagation of Financial Shocks: The Case of Venture Capital - Townsend, Richard R. (Management Science, 2015)
This paper investigates how venture-backed companies are affected when others sharing the same investor suffer a negative shock. In theory, companies may be helped or hurt in this scenario. To examine the topic empirically, I estimate the impact of the collapse of the technology bubble on non-information-technology (non-IT) companies that were held alongside IInternet companies in venture portfolios. Using a difference-in-differences framework, I find that the end of the bubble was associated with a significantly larger decline in the probability of raising continuation financing for these non-IT companies in comparison to others. This does not appear to be driven by unobservable company characteristics such as company quality or IT relatedness; for the same portfolio company receiving capital from multiple venture firms, investors with greater Internet exposure were significantly less likely to continue to participate in follow-on rounds. This paper was accepted by Itay Goldstein, operations management.